Synchronizing Two Superconducting Qubits through a Dissipating Resonator - Benedetto Militello; Anna Napoli (Entropy, 2021)
A system consisting of two qubits and a resonator is considered in the presence of different sources of noise, bringing to light the possibility of making the two qubits evolve in a synchronized way. A direct qubit–qubit interaction turns out to be a crucial ingredient, as well as the dissipation processes involving the resonator. The detrimental role of the local dephasing of the qubits is also taken into account.